Dini ya Israel
Shelf no.
A Christian religious group founded by a Maragoli in 1942.The adhere nts wear white turbans and white gowns with Israel printed over the lef t breast.
AR/MAK PHOTOS/21/1
English
Keywords: Photos of Kenya